2001
DOI: 10.1046/j.1365-2613.2001.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of IFNγ on the hepatocyte: cell cycle and apoptosis

Abstract: Summary. The inflammatory cytokine interferon gamma (IFNg) can cause cell cycle arrest and apoptosis in the hepatocyte. Primarily these processes are protective but in chronic liver disease oncogenic mutations may prosper. IFNg signalling is discussed showing how p53 is induced to cause cell cycle arrest. While caspases are are known to be responsible for IFNg induced apoptosis, how they are activated is unclear. Potential mechanisms are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…23,24 However, p53 protein levels did not increase in cells exposed to either IFN-␥ or IFN-␥/TNF (Fig. 4B).…”
Section: Differential Effects Of Ifn-␥ On Hepatocyte Andmentioning
confidence: 89%
See 1 more Smart Citation
“…23,24 However, p53 protein levels did not increase in cells exposed to either IFN-␥ or IFN-␥/TNF (Fig. 4B).…”
Section: Differential Effects Of Ifn-␥ On Hepatocyte Andmentioning
confidence: 89%
“…IFN-␥ is also inhibitory to DNA replication in primary hepatocytes (data not shown). 23,24 Because of the low proliferative capacity of primary hepatocytes and the loss of some plasma membrane receptors that occur during hepatocyte isolation, we performed the work using well-characterized cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…This lymphokine has been shown to be directly implicated in the pathogenesis of hepatic damage in a model of chronic liver injury [6]. IFN-c may cause apoptosis via IFN regulatory factor-1 (IRF-1) [26], but besides a potential direct effect of IFN-c on cell death, enhanced release of inflammatory cytokines such as TNF-a may also indirectly enhance apoptosis. In a previous study our group demonstrated that exposure to CpG-ODN followed by a second stimulus cause an IFN-c dependent increase of the inflammatory response potentially by upregulation of TLR4 in the liver [5].…”
Section: Discussionmentioning
confidence: 99%
“…IRF-1, as one of the genes the transcription of which is up-regulated by STAT1, is known to mediate apoptosis as well as cell cycle arrest in IFN-␥ responses (49). Although caspase induction has been suggested as a possible downstream event following IRF-1 induction in IFN-␥-induced apoptosis (47), studies using IRF-1-deficient mice have shown that p53 and p21 are associated with IRF-1 action in IFN-␥-induced cell cycle arrest (50). IRF-1 was also an important player in microglial apoptosis by mediating NO production (12,51).…”
Section: Discussionmentioning
confidence: 99%